Evaluasi Penerapan Metode Problem-based Learning untuk Motivasi Siswa dalam Mata Pelajaran Informatika di SMA Kabupaten Klaten - Hendarjo Hendarjo (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2022)
The current use of information and communication technology in education still needs to be more attractive to students. With this, the researcher conducted research activities to increase student motivation in informatics subjects using the Problem-Based Learning method in the Klaten district high school. Classroom Action Research was used to collect data with class X students at one of the high schools in the Klaten district, totalling fifteen students. Purposive sampling techniques were used in data sampling, observation, and interviews. This study used one cycle with descriptive data analysis techniques. The study results showed an increase in the motivation of class X students in informatics subjects at the Klaten district high school using the Problem-Based Learning method.